(untitled) (Dhaka University Journal of Science, 2023)
ZnO-Cu2O composites were prepared by precipitation technique followed by calcination. The prepared composite was characterized by scanning electron microscopy (SEM), energy dispersion X-ray (EDX), Fourier transform infra-red (FT-IR) and X-ray diffraction (XRD). Band gap energy of the composite was determined by UV-visible reflectance measurement. The absorption range of the ZnO-Cu2O composite was shifted to the visible region due to the doping of Cu2O. SEM image represented that composite nanoparticle was smaller in size compared to the pure ZnO. The EDX spectral analysis showed that no elements other than Zn, Cu and O were present in the sample. XRD showed that ZnO-Cu2O composite was made of hexagonal ZnO and cubic Cu2O. The photocatalytic activity of ZnO-Cu2O composite was studied by degrading MB under different experimental conditions. The molar ratios of the composites, amount of the composite, initial concentration of dyes were varied to optimize the conditions for degradation. The experimental result was compared with those of commercial ZnO. It was found that the ZnO-Cu2O composite is a better photocatalyst than ZnO under visible light. Dhaka Univ. J. Sci. 71(1): 42-48, 2023 (Jan)